STUDI FENOMENOLOGI: PENYINTAS COVID-19 DI KECAMATAN KROYA KABUPATEN INDRAMAYU - Alvian Pristy Windiramadhan (Universitas Prima Indonesia, 2022)
The Coronavirus-19 disease was first discovered in Wuhan, China in December 2019. This virus quickly spread to various countries, one of which was Indonesia. People infected with Covid-19 will experience complex problems. The purpose of this study is to explore more deeply about the life experiences of people infected with Covid-19. This study used a qualitative research design with a descriptive phenomenological approach. Data were taken by interview seven participants used indepth interview techniques, then the research results were analyzed used the Colaizzi method. The results of the research on the life experiences of survivor Covid-19 in Kroya Subdistrict, Indramayu Regency are described in four themes, namely: 1) Felt helpless when they know they are positive for Covid-19, 2) Felt difficult to undergo independent isolation, 3) Motivated to recover, 4) Take care not to get infected with Covid-19 again. The four themes can be interpreted that the meaning of the life experiences of people infected with Covid-19 are pleasant and unpleasant experiences when they were initially positive for being infected with Covid-19, underwent isolation, and negative from the Coronavirus.